Enhanced diagnostic utility achieved by myocardial blood analysis: A meta-analysis of noninvasive cardiac imaging in the detection of functional coronary artery disease. (15th October 2016) - Dai, Neng; Zhang, Xianlin; Zhang, Yi; Hou, Lei; Li, WeiMing; Fan, Bing; Zhang, TianSong; Xu, YaWei
Abstract: Aim: The aim of this study is to determine the diagnostic utility of 6 cardiac imaging modalities using fractional flow reserve (FFR) as the reference standard. Methods: Studies reporting diagnostic performance of computed tomographic perfusion imaging (CTP), fractional flow reserve derived from computed tomography (FFRCT ), cardiac magnetic resonance (CMR), positron emission tomography (PET), single-photon emission computed tomography (SPECT) and dobutamine stress echocardiography (DSE) for diagnosis of ischemia-causing lesions were included. Results: On vessel-based and patient-based analyses, CMR, PET, CTP and FFRCT exhibited comparable sensitivity (per-vessel: 87% vs. 86% vs. 89% vs. 86%; per-patient: 88% vs. 90% vs. 88% vs. 90%, P > 0.05) and specificity (per-vessel: 89% vs. 88% vs. 89% vs. 83%; per-patient: 84% vs. 84% vs. 87% vs. 75%, P > 0.05); whereas SPECT yielded significantly lower sensitivity (per-vessel: 72%; per-patient: 78%, P < 0.05) and specificity (per-vessel: 79%; per-patient: 79%, P < 0.05) and DES yielded significantly lower sensitivity (per-vessel: 62%, per-patient: 69%, P < 0.05). On the other hand, within the same imaging modality, myocardial blood flow (MBF) derived by CTP had a higher sensitivity (90% vs. 80%, P = 0.048) but lower specificity (77% vs. 93%, P = 0.02) than that of perfusion defect (PD). Moreover, MBF derived by CMR had a lower specificity than that of PD (60% vs. 93%, P = 0.02), while coronary flow reserve (CRF) derived by PET had a lower specificity than that of MBF (81% vs. 89%, P = 0.005). Conclusion: CMR, PET, CTP and FFRCT expressed similar and high accuracy in detecting functional CAD, whereas different analysis methods for each imaging modality may vary their diagnostic utility.